Culturally responsive integrated health care: Key issues for medical education. (July 2015) - Illes, Rose Anne C; Grace, Aaron J; Niño, José R; Ring, Jeffrey M
Primary care providers are increasingly responsible for providing mental health care in the United States. For those patients who do receive specialty mental health services, the primary care provider functions as the main entry point into the mental health system. Given the persistent racial and ethnic health disparities in the United States, it is not surprising that mental health disparities also present a difficult challenge for both the U.S. health system and for frontline practitioners. Physicians-in-training require tools for rapid psychiatric assessment that will quickly identify pertinent symptom clusters and distinguish between major psychological disorders. It is incumbent on residency faculty to teach resident physicians how to provide culturally responsive mental health assessment and intervention/referral knowledge and skills toward the elimination of these disparities and toward patient-centered care. This article begins with an overview of health disparities and barriers to health and mental health care access, followed by a discussion of culturally responsive care including an example of a culturally responsive educational program in the United States that is directly targeting the problem of access in that geographic region. It concludes with a review of educational strategies for enhancing culturally responsive behavioral and mental health care by physicians in training.